A Function-Separated Design of Electrode for Realizing High-Performance Hybrid Zinc Battery - Zhong, Yijun; Xu, Xiaomin; Liu, Pengyun; Ran, R.; Jiang, San Ping; Wu, Hongwei; Shao, Zongping (WILEY-V C H VERLAG GMBH, 2020)
A rechargeable hybrid zinc battery is developed for reaching high power density and high energy density simultaneously by introducing an alkaline Zn–transition metal compound (Zn–MX) battery function into a Zn–air battery. However, the conventional single-layer electrode design cannot satisfy the requirements of both a hydrophilic interface for facilitating ionic transfer to maximize the Zn–MX battery function and a hydrophobic interface for promoting gas diffusion to maximize the Zn–air battery function. Here, a function-separated design is proposed, which allocates the two battery functions to the two faces of the cathode. The electrode is composed of a hydrophobic MnS layer decorated with Ni–Co–S nanoclusters that allows for smooth gas diffusion and efficient oxygen electrocatalysis and a hydrophilic NixCo1−xS2 layer that favors fast ionic transfer and superior performance for energy storage. The battery with the function-separated electrode shows a high short-term discharge voltage of ≈1.7 V, an excellent high-rate galvanostatic discharge–charge with a power density up to 153 mW cm−2 at 100 mA cm−2, a good round-trip efficiency of 75% at 5 mA cm−2, and a robust cycling stability for 330 h with an excellent voltage gap of ≈0.7 V at 5 mA cm−2.